2021
DOI: 10.1002/etc.4962
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxic Effects Caused by Occupational Exposure to Agrochemicals in a Region of Northeastern Brazil: A Cross‐Sectional Study

Abstract: The objective of the present study was to evaluate the renal function of rural workers in a city of northeastern Brazil. A cross‐sectional study was carried out with 208 workers in Boquim, Sergipe, Brazil. Renal function markers and butyrylcholinesterase (BChE) were evaluated and the glomerular filtration rate (GFR) was determined. The sample consisted mainly of illiterate males with a low usage of personal protective equipment and no training. Approximately 40% had some level of renal failure. Relative risk (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
1
5
0
1
Order By: Relevance
“…In terms of renal function, eGFR was found to be lower in the male farmers who used pesticides. This significant difference was in agreement with previous findings for pesticide-exposed individuals, in which associations with lower eGFR were observed for organophosphates and carbamates, as well as herbicides such as atrazine and glyphosate [ 33 , 34 , 35 , 36 ]. Organophosphate exposure may alter the glomeruli, as well as the proximal and distal tubules [ 46 , 47 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In terms of renal function, eGFR was found to be lower in the male farmers who used pesticides. This significant difference was in agreement with previous findings for pesticide-exposed individuals, in which associations with lower eGFR were observed for organophosphates and carbamates, as well as herbicides such as atrazine and glyphosate [ 33 , 34 , 35 , 36 ]. Organophosphate exposure may alter the glomeruli, as well as the proximal and distal tubules [ 46 , 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…Exposure to certain pesticides may also increase the risk of end-stage renal disease [ 32 ]. Several studies have observed associations between exposure to herbicides and insecticides, including carbamates and organophosphates, and a lower estimated glomerular filtration rate (eGFR) [ 33 , 34 , 35 , 36 ]. Kidney function alterations have been reported in Thai farmers who use organophosphates and carbamates, depending on their use of PPE [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Um estudo recente mostra que a mortalidade por insuficiência renal aguda (IRA) está aumentando em regiões urbanas e rurais, principalmente entre trabalhadores agrícolas de áreas rurais com maior consumo de agrotóxicos, trabalhadores mais jovens, mulheres e moradores do sul do Brasil 51 . Outro estudo com agricultores brasileiros observou a falta de uso de equipamento de proteção individual (EPI) e pouca capacitação ocupacional, e constatou que trabalhadores com mais de 5 anos de exposição a agrotóxicos apresentaram maior risco relativo de alteração da TFG (RR 1,59) 52 .…”
Section: Metaisunclassified
“…In addition to Central America and Sri Lanka, hundreds of occupational renal disease studies were reported after 1990 -excluding heavy metals- in other low and middle-income countries ( Table 4 ), like India, Thailand, China, Indonesia and Nepal in Asia, Egypt, Kenya, Malawi, Ghana, Nigeria, Morocco and South Africa in the African continent, Lebanon, Turkey and Iran in the Middle-East, Bulgaria in Europe, Mexico in North America and Cuba, Argentine and Brazil in South America ( 22 , 80 , 94 , 95 , 233 261 ).…”
Section: Occupation and The Kidneymentioning
confidence: 99%
“…Papers from Brazil emphasized the association between kidney disease and pesticides ( 261 ). A systematic review of Prudente et al.…”
Section: Occupation and The Kidneymentioning
confidence: 99%